(untitled) (Fiep Bulletin - online, 2024)
Introduction: Digital media constitute a valuable source of information for research development. The visibility given to school parasports through the Instagram digital media is the subject of this article. Objective: The objective was to understand how the theme of school parasports is presented on the official profile of the Brazilian Paralympic Committee (CPB) on Instagram, through its thematic characterization, publication frequency, and user engagement. Methods: This documentary, descriptive, and quantitative research analyzed CPB’s Instagram publications on school parasports from 2017 to 2019. For data collection, the official CPB Instagram page was accessed. The publications on the theme were recorded in an electronic spreadsheet that enabled data analysis. Results: 2.513 publications were identified, of which 333 were about school parasports, indicating the relevance attributed to the school parasports theme compared to the total of other publications and the visibility users give to the terms (likes). Regarding the frequency of occurrences by subjects of publications during the analyzed period, 13,25% of publications, compared to the overall, were about school parasports, so it can be stated in this context that CPB gives little visibility to the theme. Conclusion: The school parasports theme, on CPB’s Instagram account, appears to have low visibility (n=333), and the publications on school parasports focused on the offering of projects and events for children, adolescents, and young people.